2019
DOI: 10.1104/pp.19.00448
|View full text |Cite
|
Sign up to set email alerts
|

A Mutant Allele Uncouples the Brassinosteroid-Dependent and Independent Functions of BRASSINOSTEROID INSENSITIVE 1

Abstract: Plants depend on various cell surface receptors to integrate extracellular signals with developmental programs. One of the beststudied receptors is BRASSINOSTEROID INSENSITIVE 1 (BRI1) in Arabidopsis (Arabidopsis thaliana). Upon binding of its hormone ligands, BRI1 forms a complex with a shape-complementary coreceptor and initiates a signal transduction cascade, which leads to a variety of responses. At the macroscopic level, brassinosteroid (BR) biosynthetic and receptor mutants have similar growth defects, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 36 publications
(63 reference statements)
1
23
0
Order By: Relevance
“…Quantification of aberrant cell walls in cortex cells revealed that the majority of bri1-116 meristems had a least one oblique cortex cross wall per median confocal section, a phenotype which was enhanced in bri-triple mutants (Figure 5B). We recently reported that some functions of BRI1 are independent of classical BR signalling outputs (Holzwart et al, 2018; Holzwart et al, 2019). However, cell shape defects in bri1 mutants seem to be caused by reduced BRI1/ligand dependent signalling, as the biosynthetic mutants cpd (Szekeres et al, 1996) and det2 (Chory et al, 1991), as well as plants in which endogenous BRs were depleted by the application of brassinazole (BRZ) (Asami et al, 2000), displayed phenotypes comparable to bri1 mutants (Figure 5B).…”
Section: Resultsmentioning
confidence: 99%
“…Quantification of aberrant cell walls in cortex cells revealed that the majority of bri1-116 meristems had a least one oblique cortex cross wall per median confocal section, a phenotype which was enhanced in bri-triple mutants (Figure 5B). We recently reported that some functions of BRI1 are independent of classical BR signalling outputs (Holzwart et al, 2018; Holzwart et al, 2019). However, cell shape defects in bri1 mutants seem to be caused by reduced BRI1/ligand dependent signalling, as the biosynthetic mutants cpd (Szekeres et al, 1996) and det2 (Chory et al, 1991), as well as plants in which endogenous BRs were depleted by the application of brassinazole (BRZ) (Asami et al, 2000), displayed phenotypes comparable to bri1 mutants (Figure 5B).…”
Section: Resultsmentioning
confidence: 99%
“…An increasing body of evidence suggests BRI1 has functions that are independent of classical brassinosteroid signaling outputs mediated by the canonical brassionsteroid signaling pathway, that are mediated by receptor-like protein 44 (RLP44), which probably acts as a scaffold promoting association of BRI1 and BAK1/SERK3 [ 103 ]. RLP44 is under transcriptional control of BRI1 and is able to promote activity of a complex containing PSKR1, through an analogous scaffolding mechanism as observed for the activation of brassinosteroid signaling [ 104 ], with BRI1 and PSKR1 likely competing for RLP44 [ 105 ]. This is of interest as both BRI1 and PSKR1 contain moonlighting guanylate cyclase function that may result in cGMP-enriched scaffold complexes.…”
Section: Moonlighting Kinasesmentioning
confidence: 99%
“…RLP44 directly interacts with both BRI1 and BAK1 and promotes their association (Holzwart et al, 2018). However, RLP44 also interacts with and promotes the activity of the receptor complex for the plant growth peptide phytosulfokine (PSK) (Holzwart et al, 2018, 2020; Sauter, 2015). The interaction between RLP44 and the PSK receptor PSKR1 is important for the maintenance of procambial cell fate, as both RLP44 and PSK-related mutants show ectopic xylem formation in the position of the procambium in seedling roots (Holzwart et al, 2018, 2020).…”
Section: Introductionmentioning
confidence: 99%